Role of Vitamin D Glucosiduronate in Calcium Homeostasis - Nagubandi, Sreeramulu (1980)
Evidence has been presented suggesting the presence of vitamin D(3) 3β-glucosiduronate and 1,25-dihydroxyvitamin D(3) glucosiduronate in rat bile. To evaluate the role of vitamin D glucosiduronates in calcium and phosphorus homeostasis, we synthesized vitamin D(3) 3β-glucosiduronate and tested its biological activity in calcium- and vitamin D-deficient rats. After the intravenous administration of vitamin D(3) 3β-glucosiduronate to rats maintained on a low calcium diet, there was an increase in duodenal calcium transport and an increase in serum calcium. Vitamin D(3) 3β-glucosiduronate, however, was less active than equimolar amounts of vitamin D(3). At doses of less than 0.65-1 nmol per rat, the conjugate exhibited no activity. When vitamin D(3) 3β-glucosiduronate was administered to vitamin D-deficient rats, 25-hydroxyvitamin D was detected in the serum; the increase in serum 25-hydroxyvitamin D levels was less than that observed after the administration of an equimolar amount of vitamin D(3). Vitamin D(3) 3β-glucosiduronate showed no detectable activity in the induction of calcium binding protein in chick embryonic duodena, a system in which no endogenous steroid β-glucuronidase activity is detectable. These data demonstrate that vitamin D(3) 3β-glucosiduronate is biologically active in vivo and that the observed activity is due to hydrolysis of the conjugate to vitamin D(3). As vitamin D(3) 3β-glucosiduronate is excreted in the bile of rats, it is possible that this conjugate is reutilized in vivo after hydrolysis to free vitamin D(3). These results suggest the existence of a mechanism for reutilization of the biliary products of vitamin D(3).